PENGARUH KREATIVITAS DAN INOVASI TERHADAP KINERJA PEMASARAN PADA PT. PERKEBUNAN NUSANTARA II TANJUNG MORAWA - Cindy Margareta; Kristanty Nadapdap; Tiur Rajagukguk (CV. Armas Suan Sejahtera, 2024)
The purpose of this research is to analysis the influence of creativity and innovation to the product marketing in PT. Perkebunan Nusantara II (Persero) Tanjung Morawa. The method used in sampling was total sampling to 53 person respondent. The result of the research by parcial creativity has positive influence to the product marketing with regression coefficient 0,653, the same with it innovation has positive influence to the product marketing. The result of the research by simultant creativity and innovation influence to the marketing product because Fhitung > Ftabel, with value 7,286 > 3,18.